A Study of Assessment of Maternal Health Service Utilization in Rural Area of Surat District by Multi Indicator Cluster Survey - Shah, Hitesh; Desai, Binita; Chaudhari, Vipul; Kantharia, S L (National Journal of Community Medicine, 2013)
Introduction: Multi Indicator Cluster Survey (MICS) method is popular for assessment of health service coverage. Aims and objectives: To know utilization of health care services among women who delivered in last year (2010-11). Methodology: Cluster sampling methodology was used to select 30 clusters. In each cluster minimum 8 women who delivered in last year were interviewed for maternal health service utilization indicators like ANC services, Intra natal services and PNC services. Result: 96.35% women received at least ANC services. Approximately one out of five deliveries was home deliveries and rate of caesarean section was 12.8%. Approximately half of women were visited for post natal care by government health providers. Conclusion: Iron folic acid consumption and promotion of institutional delivery were key issues. Quality of maternal health care services remains an issue and should be strengthened to improve maternal indicators.